IDENTIFYING AND PRIORITIZING THE FACTORS AFFECTING THE USE OF E-COMMERCE IN SMALL AND MEDIUM-SIZED ENTERPRISES - Souri, Farbod (The journal of contemporary issues in business and government, 2021)
In today’s world, developed and developing countries are all aware of the importance of small and medium-sized businesses for economic growth and development. Such businesses have also attracted the attention of researchers in recent decades due to their large share in GDP, job creation and reduction of economic problems. Given the impact of small and medium-sized enterprises on economic growth and development and revenue growth, the need for growth of such companies is becoming more and more apparent that one of the ways to develop them is to use e- commerce. Therefore, considering the importance of the issue, the present paper has identified and prioritized the factors affecting the use of e-commerce in small and medium-sized enterprises in Iran. The statistical population of this study consists of senior and middle managers of small and medium-sized enterprises located in Tehran. By using random sampling method, 130 people were selected as a statistical sample. With the help of a researcher-made questionnaire, the necessary information was collected and analyzed by using SPSS software version 24. The results of the analysis of research hypotheses show that there is a significant positive relationship between technological factors and e-commerce. The correlation between organizational factors and e-commerce is also confirmed. In addition, the relationship between environmental factors and e-commerce is confirmed. Finally, other results show that the use of e-commerce can affect business performance.